Drones providing live video to dispatch centers during time-critical incidents - M. Kristiansson; M. Andersson Hagiwara; L. Svensson; S. Schierbeck; Y. Khalid; P. Lundgren; C. Magnusson; P. Nordberg; J. Hollenberg; M. Ringh; S. Forsberg; A. Claesson (BMC Emergency Medicine, 2026)
Abstract Background Early triage of emergency calls at dispatch centres relies mainly on verbal information, which may not reflect the complexity and severity of a situation, limiting dispatchers situational awareness and early decision-making. Real-time live-video could potentially be provided by drones before the arrival of emergency medical services and fire department. The aim was to evaluate feasibility and operational value of automated beyond visual line of sight (BVLOS) drones delivering early live-video to emergency dispatch centres during time-critical incidents. Methods This prospective interventional feasibility study was conducted in the region of western Sweden between 7th May–7th November 2025. One drone system with automated external defibrillator and a high-resolution camera was integrated into regional medical/fire dispatch centers, covering a 141 km 2 suburban area (population approx 63 000) enabling real-time videofeed during emergency 112-calls. The drone was dispatched to consecutive alerts meeting predefined criteria (out-of-hospital cardiac arrest, traffic accidents, fires). Outcomes included time delays, characteristics of drone- and video transmission together with dispatcher-perceived value assessed through surveys. Results Of 169 alerts, the drone system was operational in 120 (71%). Within this operational population, the drone was deployed in 56/120 alerts (47%). Eleven alerts were subsequently cancelled following updated dispatch information, leaving 45 completed alerts in which the drone arrived on scene and delivered live video to the dispatch centres. The drone arrived first or was the only resource on scene in 44/45 completed alerts (98%), with a median dispatch-to-arrival time of 4:24 min compared with 8:50 min for responding ground units ( p < 0.001). Video was transferred to dispatch centres in all (100%) completed alerts and was uninterrupted in 91%. Emergency medical dispatchers reported low/moderate value in 79% of incidents, and high value in 21% ( n = 33), with a median score of 3.0 (IQR 1.0–5.0) on a 0–10 scale. Fire dispatchers reported low/moderate value in 33% and high value in 66% ( n = 6), median 7.0 (IQR 5.5–9.3) on the same scale. No adverse events were reported. Conclusion Deployment of a BVLOS drone to diverse time-critical emergencies is operationally feasible and demonstrates a clear arrival time advantage over ground responders. Perceived operational utility varies between dispatcher groups, with fire and rescue services deriving the greatest tactical benefit from early aerial situational awareness. These findings indicate potential for future drone-integration into emergency response systems.